Factors Affecting The Acceptance of Going Concern Audit Opinions (Study on Companies Listed on IDX) - Saputra, Irvan Pratama (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2022)
This study aims to investigate the variables that affect how going concern opinions are received. The variables include audit quality, company size, and debt default. The research method is quantitative. The research population is companies in the property, real estate, and building construction sectors that are listed on the Indonesia Stock Exchange. The sampling method is purposive sampling and samples are taken 64 observation data. The study's findings demonstrate that audit quality has no impact on the likelihood of receiving going-concern audit opinions, whereas firm size has a positive impact on the likelihood of receiving going-concern audit opinions. Debt default has no impact on the likelihood of receiving going-concern audit opinions.